The mechanism of action and therapeutic potential of tumor-associated macrophages in tumor immune evasion - Wang, Kehua; Zhang, Xu; Li, Aiqin; Qiao, Xia; Xu, Yanan (Frontiers in Immunology, 2025)
Tumor-associated macrophages (TAMs) play a multifaceted role in tumor progression. As specialized immune cells, macrophages are capable of phagocytosis and digesting foreign substances, as well as removing harmful substances including cellular debris and tumor cells. Under specific pathological conditions, circulating monocytes can be recruited into the tumor microenvironment and differentiate into TAMs. Macrophages are generally polarized into two distinct subpopulations: classically activated macrophages (M1) and alternatively activated macrophages (M2). TAMs constitute a significant proportion of the mononuclear leukocyte population in solid tumors, exhibiting a complex and dualistic relationship with tumor cells. Substantial evidence indicates that TAMs can interact with tumor cells, facilitating their immune evasion while promoting invasion and metastasis. This review focuses on the mechanism and regulation of macrophages in the immune response to tumor cells, as well as various macrophage-based tumor-targeted therapeutic strategies. It will provide a reference for research on macrophage-centered therapy strategies and their application in clinical practice.